Djibouti : Technical Assistance Report-Financial Soundness Indicators Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance Report on Djibouti provides details of IMF mission to aid on the financial soundness indicators (FSI). The mission achieved the said objectives and assisted the Banking Supervision Unit (BSU) officials in the preparation of the FSI production files and the development of the metadata files. The mission held constructive discussions with the Central Bank of Djibouti staff on various other aspects of the production of statistics aimed at improving the quality of the data produced. These discussions led to the preparation of an action plan identifying the main improvements to be pursued or undertaken, with the following priority recommendations. The report also highlights that the microfinance sector is growing in Djibouti; however, access to financing remains very limited. A review of the Call Report forms revealed a number of inconsistencies. The report recommends that the BSU staff participate regularly in the FSI courses organized by the IMF.